Adenosine‐induced transient hypotension for carotid artery injury during endoscopic skull‐base surgery: case report and review of the literature. Issue 9 (10th July 2019) - Fastenberg, Judd H.; Garzon‐Muvdi, Tomas; Hsue, Victor; Reilly, Erin K.; Jabbour, Pascal; Rabinowitz, Mindy R.; Rosen, Marc R.; Evans, James J.; Nyquist, Gurston N.; Farrell, Christopher J.
Abstract : Background: As the management of ventral skull‐base pathology has transitioned from open to endonasal treatment, there has been an increased focus on the prevention and endoscopic endonasal management of internal carotid artery (ICA) and major vascular injury. The use of adenosine to induce transient hypotension or flow arrest has been previously described during intracranial aneurysm surgery; however, there have been no reports of the technique being used during endonasal skull‐base surgery to achieve hemostasis following major vascular injury. Methods: Case report (n = 1) and literature review. Results: A 25‐year‐old female underwent attempted endoscopic endonasal resection of an advanced right‐sided chondrosarcoma. During resection of the tumor, brisk arterial bleeding was encountered consistent with focal injury to the right cavernous ICA. Stable vascular hemostasis could not be achieved with tamponade. An intravenous bolus dose of adenosine was administered to induce a transient decrease in systemic blood pressure and facilitate placement of the muscle patch over the direct site of vascular injury. The patient subsequently underwent endovascular deconstruction of the right ICA. Conclusion: This is the first reported use of adenosine to induce transient hypotension for a major vascular injury sustained during endonasal skull‐base surgery. Based on well‐established safety data from neurosurgical application, adenosine has the potential to be used as a safe and effective adjunctive technique in similar endonasal circumstances and may represent an additional tool in the armamentarium of the skull‐base surgeon. Surgeons should consider having adenosine available when a risk of ICA injury is anticipated.